2002
DOI: 10.1891/jnum.10.2.97.52555
|View full text |Cite
|
Sign up to set email alerts
|

The Infant Care Questionnaire: Assessment of Reliability and Validity in a Sample of Healthy Mothers

Abstract: Few instruments are available to assess perceptions of competence in the specific maternal role function of infant care provider. This article reports on a methodological study of the development and evaluation of the Infant Care Questionnaire (ICQ), a self-report scale designed to measure the mother's perceptions of her abilities and competence as an infant care provider. The sample consisted of healthy low-risk primiparous and multiparous mothers (N = 164) of term infants. Principal components factor analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…Higher socioeconomic status has been associated with increased parenting self-efficacy (Coleman & Karraker, 2000;Teti & Gelfand, 1991). Multiparity has been associated with increased parenting self-efficacy and competence (Pridham et al, 1991;Secco, 2002), whereas other researchers have reported no differ-ences based on parity (Conrad et al, 1992;Tarkka, 2003). Being married, having a supportive relationship with a mate, and marital quality have been related to higher maternal self-efficacy and competence (Mercer, 1986;Porter & Hsu, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Higher socioeconomic status has been associated with increased parenting self-efficacy (Coleman & Karraker, 2000;Teti & Gelfand, 1991). Multiparity has been associated with increased parenting self-efficacy and competence (Pridham et al, 1991;Secco, 2002), whereas other researchers have reported no differ-ences based on parity (Conrad et al, 1992;Tarkka, 2003). Being married, having a supportive relationship with a mate, and marital quality have been related to higher maternal self-efficacy and competence (Mercer, 1986;Porter & Hsu, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A 13-item dimension of the Toddler Care Questionnaire, the TCQ-mom and toddler, measured toddler care competence, or self-assessed ability to care for and interact with the toddler. The mom and toddler dimension was adapted from the Infant Care Questionnaire ICQ-mom and baby dimension (Secco, 2002). Validity for the ICQ is documented in higher ICQ-mom and baby scores among multiparous, compared with primiparous, mothers and an increase in maternal infant care competence scores with time in the mothering role for both older (Secco, 2002) and adolescent mothers of healthy infants .…”
Section: Measures Of Maternal Characteristicsmentioning
confidence: 99%
“…The mom and toddler dimension was adapted from the Infant Care Questionnaire ICQ-mom and baby dimension (Secco, 2002). Validity for the ICQ is documented in higher ICQ-mom and baby scores among multiparous, compared with primiparous, mothers and an increase in maternal infant care competence scores with time in the mothering role for both older (Secco, 2002) and adolescent mothers of healthy infants . Furthermore, the ICQ-mom and baby explained a significant amount of variance (66%) in parenting stress scores of adolescent mothers (Secco & Moffatt, 2003).…”
Section: Measures Of Maternal Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies have identified factors that affect maternal role competence, and these have included mothering experience or parity (Walker, Crain, & Thompson, 1986;Mercer, 1995;Secco, in press), self-esteem, and maternal self-efficacy (Kissman, 1988;Shea & Tronick, 1988;McGrath, Boukydis et al, 1993). One study compared maternal competence perceptions of older and adolescent mothers and demonstrated lower maternal role attainment for the adolescent mothers (Mercer, 1986).…”
mentioning
confidence: 99%